A scoping review of student Athletes’ perspectives on dual career policies, provisions and challenges - De Maio, Marianna; Montenegro, Simone; Papale, Olga; Serafini, Sofia; Prestanti, Iris; Izzicupo, Pascal; Abalasei, Beatrice-Aurelia; Alonso del Hierro, Tara; Çalışkan, Burak; Di Baldassarre, Angela; Ege, Håkon; Figueiredo, Antonio José; et al. (Frontiers in Sports and Active Living, 2025)
Dual career (DC) athletes face significant challenges in balancing dual demands of academic and athletic commitments. A scoping review of 25 studies published between 2014 and 2024 included data from over 3,000 student-athletes across 23 countries, with 88.5% focused on European contexts. Most adopted qualitative (52%) or quantitative (44%) approaches, with one study (4%) using a mixed method. Findings, synthesized using PRISMA guidelines, addressed logistical, social, financial, tutorship, curricula, and policy aspects. Recurring barriers included a lack of flexible educational programs, insufficient financial aid, and limited access to proximate sports and facilities. Social support systems, such as mentorship and institutional committees, emerged as essential for engagement and reducing isolation. European athletes frequently cited the need for improved financial support, highlighting scholarships and fee waivers. During the COVID-19 pandemic, e-learning strategies supported educational adherence and reduced stress, emphasizing their potential as flexible tool for addressing DC demands. However, disparities in policy implementation and service provision persist, with studies identifying cohesive institutional strategies for DC athletes. These findings underscore the need to develop harmonized frameworks across Europe, prioritizing integrated logistical planning, expanded financial support and tailored curricula. Broader perspectives from stakeholders are needed to enable DC athletes to thrive academically and athletically.